Percepções sobre o processo de cuidar de sujeitos com paralisia cerebral - Santos, Rosane Maria dos (2015)
Introduction: the presence of a child or adolescent suffering from Cerebral Palsy alters the way of living of people around them and their family caregivers, who need to deliver them care along with their daily tasks. The intense care demand required by the person suffering from Cerebral Palsy may cause their family members to feel tired, isolated, stressed and overburdened. Objective: to identify family caregivers’ perceptions on the caring process of children and adolescents with Cerebral Palsy, patients of a teaching hospital from the Unified Health System. Method: it is a quanti-qualitative study with 50 family caregivers of children and adolescents with cerebral palsy. For data collection, a questionnaire with 39 questions was used, being 35 closed questions and 4 open ones. Zarit Burden Inventory was used. For quantitative investigation, chi-square test was applied to variable association, considering p = 0.05 as the statistical significance level. As for the qualitative approach, content analysis was carried out, according to the method proposed by Bardin. Results: family caregivers’ average age was 35.2 years, median = 34.5 and SD = 10.5 years, 94% are women, 80% are mothers, 72% claim they are married, 38% have high-school level of education, and 44% are unemployed. Moreover, 77.6% point out changes in their personal life due to care delivery, 42% refer to have their own health affected and 72% search for religious support. Regarding the burden degree, it was observed that 48% of the caregivers unfold mild burden, and 52% unfold moderate burden score. From content analysis, it is possible to infer that most caregivers have positive perceptions on the caring act, and connect their reported Quality of Life to the care recipients. As for caregivers’ rights and duties understanding, a significant number of respondents relate their own citizenship to the rights of the cared subjects. Conclusion: in spite of caregivers’ positive perceptions on delivering care to children and adolescents with cerebral palsy, it is perceived that such a practice may overload subjects who render care along the years. Thus, this may hinder their own physical, mental and social health conditions, with significant changes in their quality of life and the care recipients’. It is health professionals’ duty to develop actions in order to promote caregivers’ knowledge to empower them for care development. It is pointed out that such actions need to be carried out in order to facilitate care delivery in family context, avoiding overburden and promoting caregivers’ health while considering their personal and family history, culture, beliefs and values.